2011
DOI: 10.4314/cajeb.v7i1.69788
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation in vitro de l’activité antibactérienne de cinq plantes de la pharmacopée traditionnelle de l’Adamaoua (Cameroun)

Abstract: Dans le cadre de la valorisation de la pharmacopée africaine en général et camerounaise en particulier, des décoctions de feuilles de Ricinus communis, Harungana madagascariensis, Erigeron floribundus, Chromoleana odorata et Lantana camara ont été étudiées in vitro pour leur activité antibactérienne. Trois souches bactériennes dont Staphylococcus aureus, Escherichia coli et Bacillus subtilis souvent responsables de processus morbides ont été utilisées. Les tests ont été réalisés in vitro suivant la technique s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…The aqueous extract of L. camara is very active on E. coli with a bactericidal effect and a MIC of 25 mg/mL. This strong activity is already demonstrated in more recent studies such as that of Etchike et al (16), which demonstrated the bactericidal effect on E. coli with a MIC of (1.47×10) − 2. The same observation was already made rather by Xaserra et Sharma (1999), but this time with the essential oils of the plant.…”
Section: Discussionmentioning
confidence: 49%
“…The aqueous extract of L. camara is very active on E. coli with a bactericidal effect and a MIC of 25 mg/mL. This strong activity is already demonstrated in more recent studies such as that of Etchike et al (16), which demonstrated the bactericidal effect on E. coli with a MIC of (1.47×10) − 2. The same observation was already made rather by Xaserra et Sharma (1999), but this time with the essential oils of the plant.…”
Section: Discussionmentioning
confidence: 49%
“…3 Linear retention index taken from Adams [22] and/or NIST08 [23] for apolar columns, and from FFNSC2 [24] and/or NIST08 for polar columns. 4 Percentage values are means of three determinations with an RSD% for the main components below 5% in all cases. 5 Identification methods: std, based on comparison with authentic compounds; MS based on comparison with Wiley.…”
Section: Essential Oil Analysismentioning
confidence: 99%
“…(Asteraceae) is an herbaceous plant, 1.5 m in height, with pubescent, lanceolate leaves and flowers in yellowish panicles. In Cameroon, it is commonly found as a weed along roadsides, and it is widely used in folk medicine to treat angina, female infertility, AIDS, dental pain, headache and various diseases of microbial and non-microbial origin [1][2][3][4][5][6]. The leaf aqueous extract was proven to possess analgesic, anti-inflammatory and immunomodulatory activity [1,2], the dichloromethane extract inhibition against dermatophytes [7], and the leaf ethanolic and pentane extract antiplasmodial activity [8].…”
Section: Introductionmentioning
confidence: 99%
“…The juice of the leaves is used to cure the wound (Bissangou and Ouamba, 1997). The previous studies undertaken in other countries give it some pharmacological properties such as: analgesic, anti-inflammatory and antipyretic (Owoyele et al, 2008), antibacterial (Etchike et al, 2011;Agban et al, 2013), anti-oxidative (Kavitha et al, 2013) and antifongic (Kra et al, 2009). This is the reason why anti-inflammatory and analgesic effects of leaves of C. odorata (Asteraceae) collected in Brazzaville-Congo in this study were investigated..…”
Section: Introductionmentioning
confidence: 99%
“…However, few medicinal plants were studied scientifically at the moment. In Africa, about 80% of the populations use them in the treatment of several pathologies (Etchike et al, 2011;Epa et al, 2015). In spite of the development of synthetic drugs, the vegetable drugs in his various forms occupy a special place.…”
Section: Introductionmentioning
confidence: 99%